Assessment of the health behaviors patterns among women during pregnancy - omar, Hanaa (Iraqi National Journal of Nursing Specialties, 2019)
Objective:- Women's behavior during pregnancy which can affect the health of their infant , may be influenced by their attitude toward the pregnancy. The study was carried out to assess the pattern of health behaviors for pregnant women. Methodology: A descriptive study was carried out to select randomized (100) pregnant women attending Baghdad Teaching hospital. The data were collected through personal interview by using questionnaire form constructed for the purpose of the study. Results:- The result of the study revealed that the highest percentage of study sample were in age group (21-25) years, primary graduated and house wife . The results showed that the highest percentage( 64%) of them were primigravida, (72%) of them have (1-2) children and( 64% )of them had no previous history to abortion . Regarding the pattern of pregnantwomen's health behaviors about healthy food was good, while their health behaviors about the sleep ,relaxation ,exercise ,using medication herbs and health care during pregnancy were poor . Recommendation:-The study recommended establishment educational program for pregnant women's to promote their health behaviors during pregnancy in order to prevent the pregnancy and labor complications through. MCHC and mass media.